Consumer decision-making in the specialty coffee segment: investigating the interplay of brand image and perceived value among college students - Fabiola, Divya Prisila Niken; Maulani, Terra Saptina (Marketing Management Studies, 2024)
Currently, market competition conditions are increasingly tight. This encourages Luwak White Koffie to continue to strengthen its brand image to achieve the highest position in the hearts of consumers with the strategies carried out. However, the strategy implemented by Luwak White Koffie still does not guarantee that Luwak White Koffie will become consumers' main choice when buying instant coffee. This research aims to determine the influence of brand image and perceived value on purchase decisions of Luwak White Koffie consumers. The methods used are descriptive methods and verification methods. In determining the sample technique using non-Probability Sampling techniques with a purposive sampling approach. In collecting primary data, researchers used consumer responses distributed through questionnaires regarding the Brand Image and Perceived value variables on Purchase Decisions for Luwak White Koffie consumers. The data analysis used in this research is Normality Test analysis, Multicollinearity Test at the 5% or 0.05 level, and the software application used to analyze primary data is IBM SPSS Statistics 27.0.1. The results of this research show that the F test or ANOVA test obtained a calculated f value of 128.820, then the ftable value with degrees of freedom in the numerator 2 and denominator 97 at ? (0.05) was 3.09. Next, the T test shows that tcount is 2.127 > ttable 1.984, which means Ho is rejected and Ha is accepted. It can be said that Brand Image is positive and significant in purchasing decisions. tcount 8.433 > ttable 1.984 which means Ho is rejected and Ha is accepted. It can be said that Perceived Value is positive and significant towards Purchase Decision. Thus, Brand Image and Perceived Value can influence the Purchase Decision for Luwak White Koffie products.